2004
DOI: 10.1177/07419325040250020501
|View full text |Cite
|
Sign up to set email alerts
|

Moving Toward Inclusive Practices

Abstract: In this article, the authors describe a change model that was developed and implemented over 3 years in 2 southern California school districts to promote inclusive practices. A study documented the change process and the impact of related district and site activities through interviews with general and special educators, administrators, and parents. Findings from the study indicate that all sites moved toward inclusive practices, with the participants reporting benefits for students with disabilities, the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 37 publications
2
71
0
7
Order By: Relevance
“…Vaughn, Elbaum and Boardman (2001) carried out a study as a result of which it was put forth that whereas expectations for academic skills from integration students were low, expectations for social skills were higher. Moreover, it is also stated in various studies that integrated education approach encouraging social-emotional skills as an inseparable part of daily education enables children to develop their social-emotional skills (Burstein, Sears, Wilcoxen, Cabello, & Spagna, 2004;Wigelsworth, Humphrey, & Lendrum, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Vaughn, Elbaum and Boardman (2001) carried out a study as a result of which it was put forth that whereas expectations for academic skills from integration students were low, expectations for social skills were higher. Moreover, it is also stated in various studies that integrated education approach encouraging social-emotional skills as an inseparable part of daily education enables children to develop their social-emotional skills (Burstein, Sears, Wilcoxen, Cabello, & Spagna, 2004;Wigelsworth, Humphrey, & Lendrum, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have indicated that general education teachers feel that they are not provided with enough time to plan for the instruction, collaboration, and cooperative teaching that is necessary to implement inclusion (Burstein et al, 2004;Ross, 2002;Santoli, Sachs, Romey, & McClurg, 2008;Wilkins & Nietfield, 2004;Zindler, 2009). The math teacher was the only participant to support the findings of these studies and that was only in respect to the amount of time allotted to planning for instruction.…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings of numerous studies, teachers feel they lack the in-class supports necessary to implement the practices that characterize inclusion (Burstein et al, 2004;Ross, 2002;Wilkins & Nietfield, 2004). In research conducted by Burstein et al, teachers reported that a key barrier to successful inclusion was the lack of support in the form of personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Educators were guided by their values, beliefs, and attitudes toward change, so they need to be convinced that a particular change is worthwhile and understand the reasons for it (Burnstein et al, 2004). The most effective approaches to change occur when educators participate in the planning and decision-making.…”
Section: Successful Inclusion Effortsmentioning
confidence: 99%